2010
DOI: 10.1108/rjta-14-01-2010-b002
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Tensile Properties of Jute / Cotton Blended Yarns Using Weibull Distributions

Abstract: Jute fibre, a natural composite of cellulose, hemicellulose and lignin, occupies the second place to cotton in economic importance. Recently many attempts have been made to produce fine jute blended yarn with other textile fibres. In this paper, the two types of jute/cotton blended yarn whose jute and cotton fibres were respectively blended at the opening and drawing stages were spun by using the ring spinning technology. The tensile properties of both blended yarn at gauge lengths from 150 mm to 500 mm were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Numerous efforts have been exerted in the degumming process using laccase. Xia et al (2008) investigated the effect of laccase in the linear density of jute fibers, obtaining the result that within 8 h there were no significant changes in linear density. Yan et al (2009) studied the degumming efficiency of laccase-media systems in kenaf fibers and concluded that after 6 h of treatment, the lignin content of kenaf decreased greatly, along with certain improvements in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been exerted in the degumming process using laccase. Xia et al (2008) investigated the effect of laccase in the linear density of jute fibers, obtaining the result that within 8 h there were no significant changes in linear density. Yan et al (2009) studied the degumming efficiency of laccase-media systems in kenaf fibers and concluded that after 6 h of treatment, the lignin content of kenaf decreased greatly, along with certain improvements in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to the hypothesis on estimating the maximum range of statistical distribution, based on this normality of the strength distribution, there is a 99% chance that the actual blended yarn strength will fall into the range of y σ ± 3 y θ . They also quantified the strength hybrid effect with a new parameter y ϑ , which predicts the deviation of the actual yarn strength from the strength predicted by the ROM.This can be expressed as (Equation21): is the critical fibre length and f l is the original fibre length(Pan & Postle, 1995).Xia et al studied the tensile properties of jute/cotton blended yarns using weibull distribution and observed that the equations based on experimental strength at 300 mm can predict the breaking strength more accurately than the equations based on experimental strength at 150 mm and 500 mm(Xia et al, 2010). Zhang et al reported that, in comparision with normal rotor spun yarn, the cotton/spandex composite yarns have higher breaking strength, breaking elongation and elastic recovery (Zhang et al, 2005).…”
mentioning
confidence: 99%